The effect of Plyometric Training in Sea Sand on Developing Muscular Endurance in under-21 Football Players - MAROUF , Said; Boumesjed , Abdelkader; zemam , abdelrahman (Journal of Sport Science Technology and Physical Activities, 2026)
The study aimed to investigate the effect of plyometric training in sea sand on developing the muscular endurance of soccer players under the age of 21. Given the nature of the study, the researchers adopted an experimental approach. The sample was divided into two homogeneous groups, each containing 10 players, for a period of nine weeks. The researchers then conducted post-tests on both samples. The results revealed statistically significant differences at a significance level of 0.05 and a degree of freedom of 9.00. This means there is a significant difference between the averages of the results, favoring the experimental group, in the muscular endurance tests.